(untitled) (Bangladesh Journal of Nuclear Medicine, 2024)
In breast cancer patients, planar bone scintigraphy is commonly used for detecting osseous metastasis. This case report emphasizes the importance of recognizing unusual extraosseous uptake in bone scintigraphy, even when negative for osteoblastic lesions. A 35-year-old post-treatment breast carcinoma patient exhibited unexpected radiotracer uptake in the upper abdomen. Subsequent SPECT/CT revealed radiotracer-avid calcified hepatic lesions and extensive non-avid metastatic lesions, however no osteoblastic metastasis. Ultrasound-guided core biopsy confirmed extensive hepatic metastases secondary to ductal carcinoma of the breast. This highlights the critical role of SPECT/CT in precisely identifying and characterizing lesions, aiding in advanced breast cancer diagnosis and management planning. Bangladesh J. Nuclear Med. 27(1): 121-126, 2024